Effects of Geological and Environmental Events on the Diversity and Genetic Divergence of Four Closely Related Pines: Pinus koraiensis, P. armandii, P. griffithii, and P. pumila - Jia, Yun; Zhu, Juan; Wu, Ying; Fan, Wei-Bing; Zhao, Gui-Fang; Li, Zhong-Hu (Frontiers in Plant Science, 2018)
The effects of mountain uplift and environmental oscillations on nucleotide variability and species divergence remain largely unknown in East Asia. In this study, based on multiple nuclear DNA markers, we investigated the levels and patterns of nucleotide diversity and interspecific divergence in four closely related pines in China, i.e., Pinus koraiensis, P. armandii, P. griffithii, and P. pumila. The four pine taxa shared low levels of nucleotide polymorphisms at the species level. P. pumila had the highest silent nucleotide diversity (πsil = 0.00661) whereas P. griffithii had the lowest (πsil = 0.00175), while the levels of genetic polymorphism in P. armandii (πsil = 0.00508) and P. koraiensis (πsil = 0.00652) were intermediate between the other two species. Population genetic structure analysis showed that variations primarily existed within populations of the four pine species, presumably due to habitat fragmentation or the island-like distributions of Pinus species. Population divergence (FST) analysis showed that the genetic divergence between P. griffithii and P. koraiensis was much greater than that between P. koraiensis and the other two pines species. Isolation-with-migration analysis suggested that asymmetric gene flow had occurred between any two pairs of pine species. Phylogenetic analyses indicated that the four allied species split into two groups about 1.37 million years ago, where P. armandii and P. pumila were closer and clustered as sister species, whereas P. koraiensis and P. griffithii were clustered on another branch. Our results and those obtained in previous studies suggest that mountain uplift and geological climate oscillations may have led to the patterns of genetic divergence and nucleotide variations in these four pine species.